Isolation and Identification Salmonella ssp from Local and Imported Chicken Meat by using VIDAS® -Up Salmonella - Alyaa Abdulhussein Kadhim (Journal of Madenat Alelem University College, 2020)
This study was carried out to isolate Salmonella species from Chicken meat, comparing the conventional method with rapid methods VIDAS ® -Up salmonella SPT (BioMérieux),  142 meat samples (Chicken) from the  Local and Imported meat From local markets in the city of Baghdad within the period Septembers  2013 -march 2014. nineteen isolates were diagnosed as genus Salmonella and ensured by National center of Salmonella in Baghdad. nineteen  Salmonella serotype (15.8 %) were diagnosed from chicken meat that  includes  S.typhimurium (% 31.5)  S.braenderup, S. dublin S. antum, and S. hadar ( 10.5 % ) for each of them and finally S.entertidis , S.livingstone and S.give  at  5.2 %  for each of them . The study recorded the serotypes of  S.give and S. living stone as  the first time in Iraq from chicken meat These results showed high significant differences at (P <0.01) between food samples. The results revealed that the contamination of  imported meat was  more than local meat and recorded of  Salmonella isolates from imported meat that higher compared with local meat  , The results Sensitivity test  eight  antibiotics (Ampicillin , Amoxycillin , cefitizdime, Chloramphenicole ,Impinem, trimethprime, Ciprofloxacin and  Ceftriaxone) were observed resistant of the serotypes isolated from food samples towards Trimethprime Cetazidime, Ampicillin, Chloromphenicol, Ceftriaxone, and Amoxicillin at (100  , 86.6 ,40,30 , 33.3  and 16.6 %)  respectively, and showed that the sensitivity for each of Imipenem and Ciprofloxacin 100%. VIDAS ® UP Salmonella  showed high values of specificity and accuracy. VIDAS ®  significantly decreased the time to obtain results  compared  to  the  conventional method  and  this  is  an  important  factor  in  the  selection  of  an  analytical method.